An Investigation into the Effects of the Contemporary Crisis of Masculinity on the Advertising of Selected Beer and Cider Brands in South Africa via Semiotic Analyses - Graham, Mia (The IIE, 2016)
Beer and cider brands are relentless in their portrayal of the hegemonic masculinity pervasive in South African society. Existing research extensively looks at the relationship between beer and masculinity. The author of this paper investigates the impact of the media on societal gender norms and the role of the media in the construction of identity. Within the context of South African contemporary advertising, beer is continually equated to hegemonic masculinity in every form, in every place, in every way. The crisis of masculinity has created a space for men to step outside of the boundaries of the hegemonic masculinity promoted throughout South African society. What this means is that there has been an increase in a variety of male audiences and advertises have had to take this into account. This paper looks at how the contemporary crisis of masculinity affects the advertising of beer and cider brands in South Africa. This is done through research into the history of masculinity (and femininity) in South Africa in order to fully understand the origins of the current hegemonic masculine society. This research will be conducted through semiotic analyses of advertisements from Savannah Dry, Black Label, Windhoek Lager, and Flying Fish. What is found is that instead of beer and cider brands embracing these newly popularised masculinities, they are rather continuing to promote the hegemonic masculinity already entrenched in South Africa. This results in the removal of women from these narratives and leaves beer and cider brands behind as the rest of the world continue to grow and challenge gender norms.
Keywords: Semiotic analyses; Hegemonic masculinity; Societal gender norms